Research on Data Assetization Difficulties and Management Path - Wang, Xichen (Frontiers in Business, Economics and Management, 2023)
With the rapid development of the digital era, data has become an important asset for enterprises and individuals. Data assetization is the process of assigning corresponding economic value to data, which plays a crucial role in the development and competitiveness of enterprises. However, in the process of implementing data assetization, enterprises face a number of difficulties and challenges, including data quality issues, data privacy and security risk issues, data governance and organizational change issues. By studying the difficulties and management paths of data assetization, this thesis discusses the challenges and solutions faced by data assetization, aiming to provide guidance and reference for enterprises to realize data assetization.